Animal people - Brown, Meghan Ann (2015)
Animal People is an ethnography of contemporary animal-centric subcultures including furry fans, zoophiles, exotic animal keepers, trophy hunters, taxidermists, horse show competitors, and pit bull advocates, inviting the reader into their hidden worlds, their desires, their culture, activities, and gatherings. These essays examine the impacts of these subcultures on individual people and animals as well as the human and animal worlds, exploring how animals function as vehicles for human desires and why humans are drawn to extremes in our relationships with them. Why do some people want to kill a lion and others want to be a lion? Why do some people want a pet lion and others want to have sex with a lion? What makes people respond to the same animal in such vastly different ways? Sociologists have largely overlooked animal-related subcultures, but there’s a lot to be to learned from knowing them. The nine subcultures described in these chapters represent the enormous variety, breadth, and depth of human relationships to animals. They have taken their relationships with animals to the edge